Saccharomyces - Peixoto Basso, Thalita; Carlos Basso, Luiz (IntechOpen, 2021)
This book examines the value of the Saccharomyces genus in areas of agriculture and pharmaceuticals. It includes seven chapters in two sections: "Agricultural and Biotechnological Applications" and "Medical and Pharmaceutical Applications." The chapters cover such topics as metabolic engineering of S. cerevisiae using CRISPR-Cas9. technology to produce biopharmaceuticals, fruit juice fermentation for antioxidant activity, mode of action of indigenous S. cerevisiae, the performance of Saccharomyces as an antiviral microorganism for pandemic diseases, application of yeast to study DNA repair and damage tolerance on cell cycle division, how calorie restriction can support the anti-aging process using yeast budding cells, and secondary metabolites from S. cerevisiae with anticancer activity.